2021
DOI: 10.3390/biomedicines9050574
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Molecular Mechanism of Water Interaction with Gelatin Methacryloyl Hydrogels: Role of Ionic Strength, pH, Drug Loading and Hydrogel Network Characteristics

Abstract: Water plays a primary role in the functionality of biomedical polymers such as hydrogels. The state of water, defined as bound, intermediate, or free, and its molecular organization within hydrogels is an important factor governing biocompatibility and hemocompatibility. Here, we present a systematic study of water states in gelatin methacryloyl (GelMA) hydrogels designed for drug delivery and tissue engineering applications. We demonstrate that increasing ionic strength of the swelling media correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 82 publications
(133 reference statements)
2
31
1
Order By: Relevance
“…35 Other studies have demonstrated that GelMA formulation parameters such as ionic strength and pH can affect cargo loading, GelMA mesh characteristics, and overall net charge. 36 Although EV/GelMA electrostatic interactions were beyond the scope of this study, EVs generally carry a net negative charge and such interactions may be an important factor to consider in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…35 Other studies have demonstrated that GelMA formulation parameters such as ionic strength and pH can affect cargo loading, GelMA mesh characteristics, and overall net charge. 36 Although EV/GelMA electrostatic interactions were beyond the scope of this study, EVs generally carry a net negative charge and such interactions may be an important factor to consider in future studies.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, MCF-7 spheroid formation was observed by day 14 of culture (Figure 7E). This was expected based on the Young's moduli of the Gel-SH/PEG-4MAL hydrogels (Figures 4 and 5), where hydrogels possessed Young's moduli similar to that of breast fat and fibroglandular tissue (roughly 2.5-3.5 kPa) [82][83][84][85]. From the conditions tested, it was observed that 5% (w/v) Gel-SH hydrogels provided the most suitable environment for spheroid formation, as spheroids appeared more frequently and greater in size in these hydrogels compared to 10% (w/v) and 2.5% (w/v) Gel-SH hydrogels.…”
Section: Resultsmentioning
confidence: 82%
“…Regarding the culture of breast cancer cells, through compression testing, Samani et al found that breast fat and fibroglandular tissues exhibited Young’s moduli of 3.25 kPa, whereas breast cancer tumors possessed Young’s moduli ranging from 6.41 kPa to 42.51 kPa, depending on the type of tumor [ 82 ]. Using alternative methods of measurement, other studies have found that breast fibroglandular tissues typically possess Young’s moduli between 2.5 kPa and 3.5 kPa [ 83 , 84 , 85 ]. Therefore, Gel-SH/PEG-4MAL hydrogels would be suited for the culture of breast cancer cells, as the Young’s moduli of breast fat and fibroglandular tissues is similar to that of Gel-SH/PEG-4MAL hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, DG-7 exhibits the lowest electrostatic repulsion between the polymer chains and therefore the tightest structure. The addition of divalent Fe ions increases the ionic strength [63,64] of the external solution resulting in a lower mesh size for Fe-7 and Fe-9 compared to DG-7 and DG-9. As an exception to the expected trend, Fe-12 shows a small increase in mesh size compared to DG-12, indicating another unknown interaction that may play a role here.…”
Section: Discussionmentioning
confidence: 99%